Polypropylene Compositions for Exterior Automotive Applications

A polypropylene composition with a mixed plastic blend, heterophasic copolymer, and ethylene plastomer addresses contamination and mechanical issues in recycled polyolefins, offering improved impact and flow properties for automotive exteriors.

JP7600440B2Active Publication Date: 2024-12-16BOREALIS AG
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023575445
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-09
Filing Date
2022-06-07
Publication Date
2024-12-16
Estimated Expiration
2042-06-07

AI Technical Summary

Technical Problem

The challenge lies in recycling post-consumer polyolefin materials for automotive exterior applications, as they are often contaminated and exhibit limited mechanical properties, odor, and emission issues, making them unsuitable for high-quality automotive components.

Method used

A polypropylene composition comprising a mixed plastic polypropylene blend, heterophasic propylene copolymer, ethylene plastomer, and inorganic filler, carefully balanced to achieve excellent mechanical properties, thermal stability, and flowability, suitable for injection molding in automotive exteriors.

Benefits of technology

The composition provides enhanced impact properties, thermal stability, and flowability, enabling the use of recycled materials in automotive exterior applications without health and safety risks, replacing sophisticated heterophasic polypropylene copolymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600440000001
    Figure 0007600440000001
  • Figure 0007600440000002
    Figure 0007600440000002
  • Figure 0007600440000003
    Figure 0007600440000003
Patent Text Reader

Abstract

A composition suitable for automotive applications obtained by blending at least components (A), (B), (C) and (D): (A) 15% to 50% by weight, preferably 18 to 44% by weight, more preferably 20 to 40% by weight of a mixed plastic polypropylene blend, (B) 20% to 50% by weight, preferably 22 to 47% by weight, more preferably 25 to 45% by weight of a heterophasic propylene copolymer, (C) 5% to 25% by weight, preferably 7 to 23% by weight, more preferably 10 to 22% by weight of an ethylene-based plastomer, and (D) 5% to 25% by weight, preferably 7 to 22% by weight, more preferably 10 to 20% by weight of an inorganic filler.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polypropylene composition comprising a mixed plastic polypropylene-based blend and an inorganic filler, particularly suitable for exterior automotive applications. [Background technology]

[0002] Compositions suitable for the automotive industry typically contain one or more polypropylene heterophasic copolymers and / or random heterophasic copolymers, and conventionally some inorganic fillers. One of the fundamental challenges in the polymer business is recycling. At the moment, the market for recyclates, especially those from household waste, commonly called PCR ("post-consumer resins"), is somewhat limited. When starting from household waste, the sorting and separation processes employed do not make it possible to prepare pure polymers, i.e. there will always be some contaminants present, or the process may even result in a blend of different polymers. With regard to polyolefins, which constitute the majority of the polymer fraction of collected household waste, complete separation of polypropylene and polyethylene is hardly possible. Recycled polyolefin materials, especially post-consumer resins, are traditionally cross-contaminated with non-polyolefin materials such as polyethylene terephthalate, polyamide, polystyrene, or non-polymeric substances such as wood, paper, glass or aluminum. To make matters worse, these post-consumer recycled polyolefin materials, although readily available on a multi-ton scale, unfortunately have limited mechanical properties and often severe odor and / or emission problems. For exterior applications in the automotive industry, materials are required that have good flow, paintability, surface appearance, and balanced mechanical properties in terms of stiffness and toughness. In recent years, market demand has expanded towards using recycled polyolefins in blends with virgin polymers to meet specific requirements. However, there is a deeply felt need to be able to dump and reuse post-consumer polyolefin recycles in end products without health and safety hazards.

[0003] Unpublished patent application European Patent Application No. 20190838.1 relates to polypropylene compositions for automotive applications that contain mixed plastic polypropylene-based blends derived from post-consumer recycled polyolefin streams, ethylene-based plastomers, and inorganic fillers, such as talc. These compositions exhibit beneficial VOC and impact properties, so that they can replace sophisticated heterophasic polypropylene copolymers in automotive applications. However, these compositions still exhibit deficiencies in mechanical properties and flowability. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention is based on the surprising finding that by carefully selecting the heterophasic propylene copolymer-based virgin component in a polypropylene-based composition containing a mixed plastic polypropylene-based blend derived from a post-consumer recycled polyolefin stream, an ethylene-based plastomer and an inorganic filler, such as talc, the polypropylene-based composition has an excellent balance of properties in terms of impact properties, thermal stability, paintability, and mechanical properties, such as tensile properties, among others, and flowability, as indicated by a high melt flow rate. Thus, the inventive composition comprising a mixed plastic polypropylene-based blend derived from a post-consumer recycled polyolefin stream is particularly suitable for injection molding applications in the automotive field, such as automotive exterior applications, and can replace sophisticated heterophasic polypropylene copolymers. [Means for solving the problem]

[0005] The present invention relates to a composition suitable for automotive applications obtained by blending at least components (A), (B), (C) and (D), (A) 15% to 50% by weight, preferably 18 to 44% by weight, more preferably 20 to 40% by weight, of a mixed plastic polypropylene blend; (B) 20% to 50% by weight, preferably 22 to 47% by weight, more preferably 25 to 45% by weight, of a heterophasic propylene copolymer, (C) 5% to 25% by weight, preferably 7 to 23% by weight, more preferably 10 to 22% by weight, of an ethylene-based plastomer; (D) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 10% by weight to 20% by weight of an inorganic filler, All percentages are given relative to the total composition. The mixed plastic polypropylene blend (A) is a crystalline fraction (CF) content determined according to CRYSTEX QC analysis in the range of 85.0-96.0% by weight, preferably in the range of 86.5-95.5% by weight, and - soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 4.0-15.0 wt.%, preferably in the range of 4.5-13.5 wt.% having The crystalline portion (CF) is quantitatively in the range of 1.0 to 10.0% by weight, preferably in the range of 1.5 to 9.5% by weight. 13 having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; the soluble fraction (SF) has an intrinsic viscosity (iV(SF)) measured in decalin according to DIN ISO 1628 / 1 at 135° C. in the range of 0.9 to 2.1 dl / g, preferably in the range of 1.0 to 2.0 dl / g, more preferably in the range of 1.1 to 1.9 dl / g, The heterophasic propylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein, Melt flow rate (MFR) of 85 to 250 g / 10 min, preferably 90 to 150 g / 10 min, more preferably 95 to 125 g / 10 min 2 (230℃, 2.16kg, ISO1133), - soluble fraction (SF) determined according to CRYSTEX QC analysis in the range of >20.0% to 30.0% by weight, and an intrinsic viscosity iV(SF) of the soluble portion measured in decalin according to DIN ISO 1628 / 1 at 135° C. of 2.0 dl / g to 4.5 dl / g, preferably 2.4 to 3.8 dl / g, more preferably 2.5 to 3.7 dl / g; having The ethylenic plastomer (C), which is a copolymer of ethylene and a comonomer unit selected from an α-olefin having 3 to 12 carbon atoms, preferably an α-olefin having 4 to 10 carbon atoms, most preferably 1-butene or 1-octene, Melt flow rate (MFR) of 0.2 to 2.5 g / 10 min, preferably 0.3 to 2.0 g / 10 min 2 (190℃, 2.16kg, ISO1133), and 850~870kg / m 3 , preferably 855 to 865 kg / m 3 Density of having The composition comprises: Melt flow rate (MFR) of 8 to 50 g / 10 min, preferably 10 to 48 g / 10 min, more preferably 11 to 45 g / 10 min 2 (230℃, 2.16kg, ISO1133) The present invention relates to a composition having the formula:

[0006] Furthermore, the present invention relates to an article, preferably a molded article, more preferably an automotive molded article, comprising the composition as described above or below.

[0007] Still further, the present invention relates to the use of the above or below described composition for injection molding of an article, preferably an automotive article, more preferably an automotive exterior article.

[0008] definition Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Although any methods and materials similar or equivalent to those described herein can be used in the practice of testing the present invention, the preferred materials and methods are described herein. In describing and claiming the present invention, the following terms are used in accordance with the definitions set forth below. Unless expressly stated otherwise, the use of terms such as "a" and "an" refers to one or more.

[0009] Mixed plastics are defined as the presence of small amounts of compounds not normally found in virgin (virgin) polypropylene blends, such as polystyrene, polyamides, polyesters, wood, paper, limonene, aldehydes, ketones, fatty acids, metals, and / or long-term degradation products of stabilizers. Virgin polypropylene blends refer to blends that originate directly from the manufacturing process without intermediate uses. As a matter of definition, a "mixed plastic" may contain detectable amounts of polystyrene and / or polyamide-6 and / or limonene and / or fatty acids. Thus, mixed plastics, in contrast to virgin polymers, may originate from both post-consumer and post-industrial sources. Post-consumer waste refers to objects that have completed at least a first use cycle (or life cycle), i.e. have already fulfilled their first purpose. In contrast, post-industrial waste refers to manufacturing scrap, or conversion scrap, which usually does not reach the consumer.

[0010] Those skilled in the art will appreciate that the soluble fraction (SF) obtained by CRYSTEX QC analysis having an intrinsic viscosity (iV(SF)) in the range of 0.9 to less than 2.2 dl / g is typically found in materials from recycle streams. In a preferred embodiment of the invention, the soluble fraction (SF) obtained by CRYSTEX QC analysis has an intrinsic viscosity (iV(SF)) in the range of 0.9 to 2.1 dl / g.

[0011] A polymer blend is a mixture of two or more polymer components. Generally, the blend can be prepared by mixing two or more polymer components. A suitable mixing procedure known in the art is post-polymerization blending. The post-polymerization blend can be a dry blend of the polymer components, such as polymer powder and / or polymer pellets via compounding, or a melt blend by melt mixing the polymer components.

[0012] Propylene homopolymer is a polymer consisting essentially of propylene monomer units. Due to impurities, particularly in commercial polymerization processes, propylene homopolymer may contain up to 0.1 mol% comonomer units, preferably up to 0.05 mol% comonomer units, and most preferably up to 0.01 mol% comonomer units.

[0013] "Polypropylene-polyethylene blend" refers to a composition containing both polypropylene and polyethylene, including polypropylene and polyethylene copolymers. Direct determination of polypropylene and polyethylene content is not possible, and the weight ratios of polypropylene (A-1) to polyethylene (A-2) of 19:1 to 7:3 represent equivalence ratios determined from calibration with iPP and HDPE and determination by IR spectroscopy.

[0014] Polypropylene means a polymer composed of greater than 50 mole % units derived from propylene. By polyethylene is meant a polymer composed of greater than 50 mole % units derived from ethylene.

[0015] The term "elastomer" refers to a natural or synthetic polymer having elastic properties. The term "plastomer" refers to a natural or synthetic polymer that combines the properties of elastomers and plastics, e.g., rubber-like properties with the processability of plastics. Ethylene-based plastomer means a plastomer composed of more than 50 mole % units derived from ethylene.

[0016] The presence of heterophasicity can be readily determined, for example, by the number of glass transitions in dynamic mechanical analysis (DMA) and / or by high-resolution microscopy such as scanning electron microscopy (SEM), transmission electron microscopy (TEM) or atomic force microscopy (AFM).

[0017] The term "XCS" refers to the cold xylene solubles (fraction) (XCS wt%) determined according to ISO 16152 at 25° C. The term "XCI" refers to the cold xylene insolubles (fraction) (XCI wt%) determined according to ISO 16152 at 25° C.

[0018] A reactor blend is a blend resulting from production in two or more reactors connected in series, or in a reactor having two or more reaction zones. Alternatively, a reactor blend may result from blending in solution. Reactor blends are in contrast to formulations such as those produced by melt extrusion.

[0019] Unless otherwise indicated, "%" refers to % by weight. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] composition In a first aspect, the present invention relates to a composition suitable for automotive applications obtained by blending at least components (A), (B), (C) and (D), (A) 15% to 50% by weight, preferably 18 to 44% by weight, more preferably 20 to 40% by weight, of a mixed plastic polypropylene blend; (B) 20% to 50% by weight, preferably 22 to 47% by weight, more preferably 25 to 45% by weight, of a heterophasic propylene copolymer, (C) 5% to 25% by weight, preferably 7 to 23% by weight, more preferably 10 to 22% by weight, of an ethylene-based plastomer, and (D) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 10% by weight to 20% by weight of an inorganic filler, All percentages are given relative to the total composition. The mixed plastic polypropylene blend (A) is a crystalline fraction (CF) content, determined according to CRYSTEX QC analysis, in the range of 85.0 to 96.0% by weight, preferably in the range of 86.5 to 95.5% by weight, and - soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of 4.0-15.0 wt.%, preferably in the range of 4.5-13.5 wt.% having The crystalline portion (CF) is quantitatively in the range of 1.0 to 10.0% by weight, preferably in the range of 1.5 to 9.5% by weight. 13 having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; the soluble fraction (SF) has an intrinsic viscosity (iV(SF)) measured in decalin according to DIN ISO 1628 / 1 at 135° C. in the range of 0.9 to 2.1 dl / g, preferably in the range of 1.0 to 2.0 dl / g, more preferably in the range of 1.1 to 1.9 dl / g, The heterophasic propylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein, Melt flow rate (MFR) of 85 to 250 g / 10 min, preferably 90 to 150 g / 10 min, more preferably 95 to 125 g / 10 min 2 (230℃, 2.16kg, ISO1133), A soluble fraction (SF) content determined according to CRYSTEX QC analysis in the range of >20.0% to 30.0% by weight, and an intrinsic viscosity iV(SF) of the soluble portion measured in decalin according to DIN ISO 1628 / 1 at 135° C. of 2.0 dl / g to 4.5 dl / g, preferably 2.4 to 3.8 dl / g, more preferably 2.5 to 3.7 dl / g; having The ethylenic plastomer (C), which is a copolymer of ethylene and a comonomer unit selected from an α-olefin having 3 to 12 carbon atoms, preferably an α-olefin having 4 to 10 carbon atoms, most preferably 1-butene or 1-octene, Melt flow rate (MFR) of 0.2 to 2.5 g / 10 min, preferably 0.3 to 2.0 g / 10 min 2 (190℃, 2.16kg, ISO1133), and 850~870kg / m 3 , preferably 855 to 865 kg / m 3 Density of having The composition comprises: Melt flow rate (MFR) of 8 to 50 g / 10 min, preferably 10 to 48 g / 10 min, more preferably 11 to 45 g / 10 min 2 (230℃, 2.16kg, ISO1133) The present invention relates to a composition having the formula:

[0021] The automotive compositions of the present invention are particularly suited for injection molding of articles for use on the exterior of a vehicle.

[0022] Compositions suitable for automotive applications according to the present invention have one or more of the following characteristics:

[0023] The composition has a melt flow rate MFR of 8 to 50 g / 10 min, preferably 10 to 48 g / 10 min, more preferably 11 to 45 g / 10 min. 2 (230℃, 2.16kg, ISO1133).

[0024] The composition can be characterized by CRYSTEX QC analysis, which provides the crystalline fraction (CF) and soluble fraction (SF), which can be quantified and analyzed for monomer and comonomer content and intrinsic viscosity (iV). The composition preferably exhibits one or all of the following characteristics in a CRYSTEX QC analysis: A crystalline fraction (CF) content determined according to CRYSTEX QC analysis in the range of 55.0 to 75.0 wt.%, preferably 60.0 to 72.0 wt.%, · Soluble fraction (SF) content, determined according to CRYSTEX QC analysis, in the range of 25.0-45.0 wt.%, preferably 28.0-40.0 wt.%.

[0025] The crystalline portion (CF) preferably has one or more, preferably all, of the following properties: Quantitative, less than 10.0% by weight, preferably 2.5-7.5% by weight 13 ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, and / or An intrinsic viscosity (iV(CF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., of less than 1.8 dl / g, preferably between 0.8 and 1.6 dl / g.

[0026] The fusible part (SF) preferably has one or more, preferably all, of the following properties: Quantitatively in the range of 45.0 to 65.0% by weight, preferably 46.0 to 63.0% by weight 13 ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, and / or An intrinsic viscosity (iV(SF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., of more than 1.6 dl / g, preferably between 1.7 and 2.7 dl / g.

[0027] The composition preferably comprises units derived from ethylene in an amount of from 12.5 to 32.5% by weight, more preferably from 15.0 to 30.0% by weight, even more preferably from 17.0 to 28.0% by weight.

[0028] The compositions according to the invention preferably exhibit an excellent balance of properties with regard to impact properties, thermal stability, flow properties as seen from the above mentioned melt flow rates, and mechanical properties, especially with regard to e.g. flexural modulus or tensile properties.

[0029] The composition preferably has a flexural modulus of 1400 MPa to 2000 MPa, preferably 1450 MPa to 1950 MPa.

[0030] Further, the composition preferably has a viscosity of 20.0 kJ / m 2~65.0kJ / m 2 , preferably 21.0 kJ / m 2 ~60.0kJ / m 2 It has a notched Charpy impact strength (CNIS at 23°C) of 1.0 to 1.5 mm at 23°C. Further, the composition preferably has a thermal conductivity of 4.0 kJ / m 2 ~10.0kJ / m 2 , preferably 4.5 kJ / m 2 ~7.5kJ / m 2 It has a notched Charpy impact strength at -20°C (CNIS at -20°C).

[0031] Even more preferably, the composition has very good impact strength in an instrumented impact test (puncture impact test). The composition preferably has a puncture energy measured at 23°C of 25-55J, preferably 30-50J. The composition preferably has an energy at maximum force measured at 23°C of 15 to 45 J, preferably 18 to 40 J. Furthermore, the composition preferably has a puncture energy measured at -30°C of 12 to 40 J, preferably 13 to 38 J. The composition preferably has a maximum impact energy measured at -30°C of 10 to 30 J, preferably 11 to 28 J.

[0032] In addition, the composition preferably has a deflection temperature under load (ISO 75B) of greater than 90°C, preferably from 91°C to 110°C.

[0033] Furthermore, the composition preferably has a coefficient of linear thermal expansion (CLTE) of 60 to 100 μm / mK, preferably 65 to 90 μm / mK.

[0034] The compositions of the present invention essentially comprise components (A), (B), (C) and (D) described above or below in the amounts correspondingly described.

[0035] The composition may optionally comprise an additional polymer component, so that the composition may be obtained by blending components (A), (B), (C) and one or more of the following components: (E) 0-20 wt.-%, preferably 0-18 wt.-%, more preferably 0-17 wt.-% of a second heterophasic propylene copolymer, and (F) 0 to 10% by weight, preferably 0 to 9% by weight, more preferably 0 to 8% by weight of a propylene homopolymer, All percentages are given relative to the total composition. The second heterophasic propylene copolymer (E) comprises a matrix phase and an elastomeric phase dispersed therein; Melt flow rate (MFR) of 2 to 10 g / 10 min, preferably 3 to 8 g / 10 min, more preferably 3.5 to 7.5 g / 10 min 2 (230℃, 2.16kg, ISO1133), a soluble fraction (SF) content determined according to CRYSTEX QC analysis of more than 20.0 to 50.0 wt.%, preferably 21.0 to 45.0 wt.%, and The intrinsic viscosity iV(SF) of the cold xylene solubles (XCS) content, measured in decalin according to DIN ISO 1628 / 1 at 135° C., is between 4.0 dl / g and 10.0 dl / g, preferably between 4.5 and 9.5 dl / g, more preferably between 5.0 and 9.0 dl / g. having Propylene homopolymer (F) is Melt flow rate (MFR) of 800 to 2000 g / 10 min, preferably 900 to 1600 g / 10 min, more preferably 1000 to 1500 g / 10 min 2 (230℃, 2.16kg, ISO1133) has.

[0036] In one embodiment, the composition is obtained by blending components (A), (B), (C) and (D), in the absence of (E) and (F); (A) 15% to 50% by weight, preferably 18 to 44% by weight, more preferably 20 to 40% by weight, of a mixed plastic polypropylene blend; (B) 30% to 50% by weight, preferably 32 to 47% by weight, more preferably 35 to 45% by weight, of a heterophasic propylene copolymer, (C) 5% to 25% by weight, preferably 7 to 23% by weight, more preferably 10 to 22% by weight, of an ethylene-based plastomer, and (D) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 10% by weight to 20% by weight of an inorganic filler, All percentages are given relative to the total composition.

[0037] In another embodiment, the composition is obtained by blending components (A), (B), (C), (D) and (E), in the absence of (F); (A) 15% to 40% by weight, preferably 18 to 37% by weight, more preferably 20 to 38% by weight of a mixed plastic polypropylene blend, (B) 20% to 50% by weight, preferably 22 to 47% by weight, more preferably 25 to 45% by weight, of a heterophasic propylene copolymer, (C) 5% to 25% by weight, preferably 7 to 23% by weight, more preferably 10 to 22% by weight, of an ethylene-based plastomer; (D) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 10% by weight to 20% by weight of an inorganic filler, and (E) 5-20 wt.-%, preferably 7-18 wt.-%, more preferably 10-17 wt.-% of a second heterophasic propylene copolymer, All percentages are given relative to the total composition.

[0038] In yet another embodiment, the composition is obtained by blending components (A), (B), (C), (D) and (F), in the absence of (E); (A) 15% to 40% by weight, preferably 18 to 37% by weight, more preferably 20 to 38% by weight of a mixed plastic polypropylene blend, (B) 20% to 50% by weight, preferably 22 to 47% by weight, more preferably 25 to 45% by weight, of a heterophasic propylene copolymer, (C) 5% to 25% by weight, preferably 7 to 23% by weight, more preferably 10 to 22% by weight, of an ethylene-based plastomer; (D) 5% by weight to 25% by weight, preferably 7% by weight to 22% by weight, more preferably 10% by weight to 20% by weight of an inorganic filler, and (F) 2 to 10% by weight, preferably 3 to 9% by weight, more preferably 4 to 8% by weight, of a propylene homopolymer; All percentages are given relative to the total composition.

[0039] Mixed Plastic Polypropylene Blend (A) The mixed plastic polypropylene blend (A) is suitably characterized by CRYSTEX QC analysis, which provides the crystalline fraction (CF) and soluble fraction (SF), which can be quantified and analyzed for monomer and comonomer content and intrinsic viscosity (iV). The mixed plastic polypropylene blend (A) exhibits the following characteristics in the CRYSTEX QC analysis: a crystalline fraction (CF) content, determined according to CRYSTEX QC analysis, in the range of 85.0 to 96.0% by weight, preferably in the range of 86.5 to 95.5% by weight, more preferably in the range of 88.0 to 95.0% by weight, and · A soluble fraction (SF) content, determined according to CRYSTEX QC analysis, in the range of 4.0-15.0 wt.%, preferably in the range of 4.5-13.5 wt.%, more preferably in the range of 5.0-12.0 wt.%.

[0040] The crystalline portion (CF) has one or more, preferably all, of the following properties: Quantitatively in the range of 1.0 to 10.0% by weight, preferably in the range of 1.5 to 9.5% by weight, more preferably in the range of 2.0 to 9.0% by weight 13 ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, and / or An intrinsic viscosity (iV(CF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., preferably in the range of 1.0 to less than 2.6 dl / g, more preferably in the range of 1.2 to 2.5 dl / g, even more preferably in the range of 1.3 to 2.4 dl / g.

[0041] The fusible portion (SF) has one or more, preferably all, of the following properties: Quantitatively, the range is preferably 20.0 to 55.0% by weight, more preferably 22.0 to 50.0% by weight, and even more preferably 24.0 to 48.0% by weight. 13 ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, and / or An intrinsic viscosity (iV(SF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., in the range of 0.9 to 2.1 dl / g, preferably in the range of 1.0 to 2.0 dl / g, more preferably in the range of 1.1 to 1.9 dl / g.

[0042] Preferably, the mixed plastic polypropylene blend (A) comprises polypropylene and polyethylene. The weight ratio of polypropylene to polyethylene is preferably 19:1 to 7:3.

[0043] The mixed plastic polypropylene blend (A) preferably contains more than 50 mole % of units derived from propylene.

[0044] The mixed plastic polypropylene blend (A) preferably comprises units derived from ethylene in an amount of 2.5 to 15.0% by weight, more preferably 4.0 to 12.5% ​​by weight, even more preferably 5.0 to 10.0% by weight.

[0045] Furthermore, the mixed plastic polypropylene blend (A) preferably has one or more, preferably all, of the following characteristics: Melt flow rate (MFR) of 8.0 to 40 g / 10 min, preferably 9.0 to 35 g / 10 min, more preferably 10.0 to 30 g / 10 min 2 (230℃, 2.16kg, ISO1133), and / or Limonene content determined by using solid phase microextraction (HS-SPME-GC-MS): 0.1 ppm to 50 ppm, and / or a tensile modulus of 1000 MPa to 1500 MPa, preferably 1100 MPa to 1400 MPa, and / or 3.0~7.5kJ / m 2 , preferably 4.0 to 7.0 kJ / m 2 Charpy notched impact strength at 23°C (CNIS at 23°C).

[0046] The mixed plastic polypropylene blend according to the present invention is preferably in the form of pellets, which contributes to a low amount of volatile materials.

[0047] Heterophasic propylene copolymer (B) The heterophasic polypropylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein.

[0048] The heterophasic propylene copolymer (B) is A melt flow rate (MFR) of 85 to 250 g / 10 min, preferably 90 to 150 g / 10 min, more preferably 95 to 125 g / 10 min 2 (230℃, 2.16kg, ISO1133), a soluble fraction (SF) content, determined according to CRYSTEX QC analysis, in the range of 20.0-30.0 wt.%, preferably 21.0-28.0 wt.%, more preferably 21.0-26.0 wt.%, and an intrinsic viscosity iV(SF) of the soluble portion measured in decalin according to DIN ISO 1628 / 1 at 135° C. of 2.0 dl / g to 4.5 dl / g, preferably 2.4 to 3.8 dl / g, more preferably 2.5 to 3.7 dl / g; It is characterized by:

[0049] Preferably, the heterophasic propylene copolymer (B) has one or more, preferably all, of the following properties: a content (C2) of units derived from ethylene in the soluble fraction (SF) of 30 to 45% by weight, preferably 32 to 40% by weight, more preferably 33 to 38% by weight, and / or a content (C2) of units derived from ethylene in the crystalline portion (CF) of 0.1 to 5.0% by weight, preferably 0.2 to 4.0% by weight, more preferably 0.5 to 3.0% by weight, and / or a total content of units derived from ethylene (C2) of 5.0 to 15.0% by weight, preferably 6.0 to 12.0% by weight, more preferably 7.0 to 10.0% by weight, and / or an intrinsic viscosity iV(CF) of the crystalline part determined according to CRYSTEX QC analysis and measured in decalin according to DIN ISO 1628 / 1 at 135°C of 0.8 to 2.0 dl / g, preferably 0.9 to 1.8 dl / g, and / or a melting temperature Tm of 155 to 175°C, preferably 157 to 172°C, more preferably 160 to 170°C, and / or a crystallization temperature Tc of 120 to 140° C., preferably 122 to 137° C., more preferably 125 to 135° C., and / or a tensile modulus of 1250 MPa to 1800 MPa, preferably 1300 MPa to 1750 MPa, more preferably 1350 MPa to 1700 MPa, and / or 4.0~8.5kJ / m 2 , preferably 5.0 to 7.0 kJ / m 2 Notched Charpy impact strength at 23°C (CNIS at 23°C).

[0050] The heterophasic propylene copolymer (B) preferably consists of propylene and ethylene units. Although not measured, the content (C3) of units derived from propylene in the soluble fraction (SF) preferably amounts to 100% by weight when combined with the content (C2) of units derived from ethylene in the soluble fraction (SF). The content (C3) of units derived from propylene in the soluble fraction (SF) is preferably 55 to 70% by weight, more preferably 60 to 68% by weight, and even more preferably 62 to 67% by weight. Although not measured, the content (C3) of units derived from propylene in the crystalline portion (CF) preferably becomes 100% by weight when combined with the content (C2) of units derived from ethylene in the crystalline portion (CF). The content (C3) of units derived from propylene in the crystalline portion (CF) is preferably 95.0 to 99.9% by weight, more preferably 96.0 to 99.8% by weight, and even more preferably 97.0 to 99.5% by weight. The total content (C3) of units derived from propylene in the heterophasic propylene copolymer (B) is preferably from 85.0 to 95.0 wt.-%, more preferably from 88.0 to 94.0 wt.-%, even more preferably from 90.0 to 93.0 wt.-%.

[0051] Such heterophasic propylene copolymers are commercially available.

[0052] Ethylene-based plastomer (C) The ethylenic plastomer (C) is preferably a copolymer of ethylene and comonomer units selected from an α-olefin having 3 to 12 carbon atoms, preferably an α-olefin having 4 to 10 carbon atoms, most preferably 1-butene or 1-octene. Ethylene-based plastomers are typically added to further improve the impact properties of the composition.

[0053] The ethylenic plastomer (C) preferably has one or more, preferably all, of the following properties: Melt flow rate (MFR) of 0.2 to 2.5 g / 10 min, preferably 0.3 to 2.0 g / 10 min 2 (190℃, 2.16kg, ISO1133), and 850~870kg / m 3 , preferably 855 to 865 kg / m 3 Density.

[0054] Such ethylenic plastomers are commercially available under trade names such as Engage, Exact, Queo, and Tafmer.

[0055] Inorganic filler (D) As the inorganic filler (D), talc is preferred.

[0056] The inorganic filler, preferably talc, (D) preferably has a median particle size (median particle size) d before compounding of 0.3 to 30.0 micrometers, more preferably 0.5 to 15.0 micrometers. 50 has.

[0057] Further, the inorganic filler, preferably talc, (D), preferably has a top-cut particle size d before compounding of 1.0 to 50.0 micrometers, preferably 1.5 to 35.0 micrometers. 95 has.

[0058] Such inorganic fillers are commercially available.

[0059] Additives Additives are commonly used in the compositions according to the invention. Preferably, the additives are selected from one or more of antioxidants, UV stabilizers, slip agents, nucleating agents, pigments, lubricants, masterbatch polymers (each of which may be plural) and / or anti-fog agents. The additives are usually present in the composition in an amount of 0.01 to 4.0% by weight, and preferably 0.05 to 3.0% by weight, based on the total weight of the composition.

[0060] Second heterophasic propylene copolymer (E) The optional heterophasic polypropylene copolymer (E) comprises a matrix phase and an elastomeric phase dispersed therein.

[0061] The second heterophasic propylene copolymer (E), if present in the composition, preferably has a melt flow rate lower than the melt flow rate of the heterophasic propylene copolymer (B). The optional second heterophasic propylene copolymer (E) has a melt flow rate MFR of 2 to 10 g / 10 min, preferably 3 to 8 g / 10 min, more preferably 4 to 7 g / 10 min. 2 (230℃, 2.16kg, ISO1133). Furthermore, the optional second heterophasic propylene copolymer (E) has a solubles (SF) content, determined according to CRYSTEX QC analysis, in the range of >20.0 to 50.0 wt.%, preferably in the range of 21.0 to 45.0 wt.%, more preferably in the range of 22.0 to 40.0 wt.%. The soluble portion preferably has an intrinsic viscosity iV(SF), measured in decalin according to DIN ISO 1628 / 1 at 135° C., of 4.0 dl / g to 10.0 dl / g, preferably 4.5 to 9.5 dl / g, more preferably 5.0 to 9.0 dl / g.

[0062] The optional second heterophasic propylene copolymer (E) preferably has a crystalline fraction (CF) content, determined according to CRYSTEX QC analysis, in the range of 50.0 to 80.0 wt.%, preferably in the range of 55.0 to 79.0 wt.%, more preferably in the range of 60.0 to 78.0 wt.%.

[0063] Preferably, the optional second heterophasic propylene copolymer (E) has one or more, preferably all, of the following properties: a content (C2) of units derived from ethylene in the soluble fraction (SF) of 25 to 35% by weight, preferably 27 to 34% by weight, more preferably 28 to 33% by weight, and / or a content of units derived from ethylene in the crystalline fraction (CF) of 0.5 to 7.5% by weight, preferably 1.0 to 5.0% by weight, more preferably 1.5 to 4.0% by weight, and / or a total content of units derived from ethylene of 4.0 to 15.0% by weight, preferably 5.0 to 12.0% by weight, more preferably 6.0 to 10.0% by weight, and / or the intrinsic viscosity iV(CF) of the crystalline part determined according to the CRYSTEX QC analysis in the range of 1.8 to 3.5 dl / g, preferably in the range of 2.0 to 3.0 dl / g, measured in decalin according to DIN ISO 1628 / 1 at 135 °C, and / or a melting temperature Tm of 155 to 175°C, preferably 157 to 172°C, more preferably 160 to 170°C, and / or A crystallization temperature Tc of 105 to 125°C, preferably 107 to 122°C, more preferably 110 to 120°C.

[0064] The optional heterophasic propylene copolymer (E) preferably consists of propylene and ethylene units. Although not measured, the content (C3) of units derived from propylene in the soluble fraction (SF) preferably amounts to 100% by weight when combined with the content (C2) of units derived from ethylene in the soluble fraction (SF). The content (C3) of units derived from propylene in the soluble fraction (SF) is preferably 65 to 75% by weight, more preferably 66 to 73% by weight, and even more preferably 67 to 72% by weight. Although not measured, the content (C3) of units derived from propylene in the crystalline portion (CF) preferably becomes 100% by weight when combined with the content (C2) of units derived from ethylene in the crystalline portion (CF). The content (C3) of units derived from propylene in the crystalline portion (CF) is preferably 92.5 to 99.5% by weight, more preferably 95.0 to 99.0% by weight, and even more preferably 96.0 to 98.5% by weight. The total content (C3) of units derived from propylene in the heterophasic propylene copolymer (B) is preferably from 85.0 to 96.0 wt.-%, more preferably from 88.0 to 95.0 wt.-%, even more preferably from 90.0 to 94.0 wt.-%.

[0065] The optional heterophasic propylene copolymer (E) preferably has a tensile modulus of from 800 MPa to 1200 MPa, preferably from 850 MPa to 1150 MPa.

[0066] Furthermore, the optional heterophasic propylene copolymer (E) preferably has a melting point of 25 to 75 kJ / m 2 , preferably 35 to 60 kJ / m 2 It has a notched Charpy impact strength (CNIS, 23°C) of 1.01 g / m2 at 23°C.

[0067] Such heterophasic propylene copolymers are commercially available.

[0068] Propylene homopolymer (F) The optional propylene homopolymer (F) preferably has a very high melt flow rate MFR of 800 to 2000 g / 10 min, preferably 900 to 1600 g / 10 min, more preferably 1000 to 1500 g / 10 min. 2 (230℃, 2.16kg, ISO1133).

[0069] Furthermore, the optional propylene homopolymer (F) preferably has a melting temperature Tm, determined by DSC according to ISO 11357-3, of 150 to 170°C, preferably of 155 to 166°C.

[0070] Such propylene homopolymers are typically added to further improve the flow properties of the composition. Such propylene homopolymers are commercially available.

[0071] Goods In another aspect, the present invention relates to an article, preferably a molded article, more preferably an automotive molded article, comprising the above or below described composition. The article is preferably for use outside a vehicle.

[0072] The article preferably exhibits paint adhesion rated as poor or delaminated coating areas. The item in question is 50 mm 2 Less than 0-45mm, preferably 0-45mm 2 , mm 2 It is preferred to have defective or delaminated coating areas of the unit.

[0073] use In yet another aspect, the present invention relates to the use of the above or below described composition for injection molding of an article, preferably an automotive article, more preferably an exterior automotive article. EXAMPLES

[0074] Experimental section The following examples are included to demonstrate certain aspects and embodiments of the claimed invention. However, it should be understood by those of ordinary skill in the art that the following descriptions are illustrative only and should not be construed as limiting the invention in any way.

[0075] Test Method a) CRYSTEX Determination of the crystalline and soluble fractions and their respective properties (IV and ethylene content) The crystalline (CF) and soluble (SF) fractions of polypropylene (PP) compositions, as well as the comonomer content and intrinsic viscosity of each fraction, were analyzed by using a CRYSTEX instrument, Polymer Char (Valencia, Spain). Details of the technique and method can be found in the literature (Ljiljana Jeremic, Andreas Albrecht, Martina Sandholzer, and Markus Gahleitner (2020) Rapid characterization of high-impact ethylene-propylene copolymer composition by crystallization extraction separation: comparability to standard separation methods, International Journal of Polymer Analysis and Characterization, 25:8, 581-596). The crystalline and amorphous parts are separated by a temperature cycle of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. Quantification of SF and CF and determination of the ethylene content (C2) are achieved by an integrated infrared detector (IR4) and for the determination of the intrinsic viscosity (iV) an online two-capillary viscometer is used. The IR4 detector detects two different bands: CH, which helps determine the concentration and ethylene content in ethylene-propylene copolymers. 3 Stretch vibration (approximately 2960cm -1 ) and CH stretching vibration (2700-3000cm -1 )) is a multi-wavelength detector that measures IR absorbance at 100 nm and 100 nm wavelengths. The IR4 detector measures ethylene content ( 13 A series of eight EP copolymers with different ethylene content (determined by C-NMR) are used to calibrate, each at different concentrations ranging from 2 to 13 mg / ml. To simultaneously address both characteristics, concentration and ethylene content, for the different polymer concentrations (Conc) expected during the Crystex analysis, the following calibration equation was applied:

[0076] Conc=a+b×Abs(CH)+c×(Abs(CH)) 2 +d×Abs(CH 3 ) + e × (Abs(CH 3 ) 2 +f × Abs(CH) × Abs(CH 3 ) (Formula 1) CH 3 / 1000C = a + b × Abs(CH) + c × Abs(CH 3 ) + d × (Abs(CH 3 ) / Abs(CH))+e×(Abs(CH 3 ) / Abs(CH)) 2 (Formula 2)

[0077] Constants a to e in Equation 1 and constants a to f in Equation 2 were determined using least squares regression analysis. CH 3 / 1000C is converted to ethylene content (wt%) using the following relationship: Weight % (ethylene in EP copolymer) = 100-CH 3 / 1000TC×0.3 (Formula 3) The amount of soluble (SF) and crystalline (CF) fractions are correlated with the amount of "cold xylene soluble" (XCS) and the cold xylene insoluble (XCI) fraction, respectively, by XS calibration, determined according to standard gravimetric methods according to ISO 16152. The XS calibration is achieved by testing various EP copolymers with XS contents ranging from 2 to 31 wt.%. The determined XS calibration is linear. Weight%XS=1.01×Weight%SF (Formula 4) The intrinsic viscosities (iV) of the parent EP copolymer as well as its soluble and crystalline parts are determined using an on-line two-capillary viscometer and correlated with the corresponding iV determined by standard methods in decalin according to ISO 1628-3. Calibration is achieved using various EPPP copolymers with iV = 2-4 dL / g. The determined calibration curve is linear.

[0078] iV(dL / g)=a×Vsp / c (Formula 5)

[0079] The samples to be analyzed are weighed out at a concentration of 10 mg / ml to 20 mg / ml. The weighed samples are packed into a stainless steel mesh MW 0.077 / D 0.05 mmm to avoid the injection of possible gels and / or polymers that are not soluble in TCB at 160°C, such as PET and PA. After autofilling the vials with 1,2,4-TCB containing 250 mg / l 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the samples are dissolved at 160° C. with constant stirring at 400 rpm until complete dissolution is achieved, typically for 60 min. The polymer solution is covered with a N2 atmosphere during dissolution to avoid sample degradation. A defined volume of the sample solution is injected into a column packed with an inert carrier where the crystallization of the sample and the separation of the soluble part from the crystalline part take place. This process is repeated twice. During the first injection, the entire sample is measured at high temperature and the iV [dl / g] and C2 [wt%] of the PP composition are determined. During the second injection, the soluble part (at low temperature) and the crystalline part (at high temperature) are measured in the crystallization cycle (wt% SF, wt% C2, iV).

[0080] b) Cold xylene solubles (XCS, wt%) The xylene cold soluble (XCS) fraction was determined according to ISO 16152; 1st edition; 2005-07-01 at 25° C. The part that remains insoluble is the xylene cold insoluble (XCI) fraction.

[0081] c) Intrinsic viscosity The intrinsic viscosity was determined according to DIN ISO 1628 / 1, October 1999 (135° C. in decalin).

[0082] d) Charpy notched impact strength 80x10x4mm prepared according to EN ISO1873-2 3 The thermal expansion coefficient was determined according to ISO 179-1eA on injection molded specimens at +23° C. and −20° C. Measurements were performed after a conditioning time of 96 hours at 23° C.

[0083] e) Flexural modulus Flexural modulus is measured on 80x10x4mm specimens prepared by injection molding according to EN ISO1873-2 3 The strength was determined according to ISO 178 for a test specimen having dimensions of (length x width x thickness), with a support distance of 64 mm, a test speed of 2 mm / min, and a force of 100 N.

[0084] f) Tensile modulus Measurements were performed according to ISO 527-2 (crosshead speed = 1 mm / min; test speed 50 mm / min, 23°C) using injection moulded specimens 1B (dogbone shape, 4 mm thick) prepared as described in EN ISO 1873-2. Measurements were performed after a conditioning time of the specimens of 96 hours at 23°C.

[0085] g) Instrumented impact test (puncture impact test) The instrumented impact test is 60 x 60 x 3 mm 3 Measurements were performed according to ISO 6603-2:2000 on injection molded plaques at 23° C. and −30° C. Measurements were performed after a conditioning period of 96 hours at 23° C. on the specimens.

[0086] h) Comonomer Content Poly(propylene-co-ethylene) - Ethylene Content - IR Spectroscopy Quantitative infrared (IR) spectroscopy was used to quantify the ethylene content of poly(ethylene-co-propene) copolymers by calibration to the primary method. 13 The calibration was facilitated by the use of a set of in-house, non-commercially available calibration standards of known ethylene content determined by C solution-state nuclear magnetic resonance (NMR) spectroscopy. The calibration procedure was performed by conventional methods well described in the literature. The calibration set consisted of 38 calibration standards with ethylene contents ranging from 0.2 to 75.0 wt% that were produced at either pilot or full scale under a variety of conditions. The calibration set was selected to reflect the typical diversity of copolymers encountered in the eventual quantitative IR spectroscopy. Quantitative IR spectra were recorded in the solid state using a Bruker Vertex 70 FTIR spectrometer. Spectra were recorded on 25 × 25 mm square films with a thickness of 300 μm prepared by compression molding at 180-210 °C and 4-6 MPa. For samples with very high ethylene content (>50 mol%), 100 μm thick films were used. Standard transmission FTIR spectroscopy was employed, ranging from 5000 to 500 cm. -1 Spectral range, 6mm aperture, 2cm -1 A spectral resolution of 16, 16 background scans, 16 spectral scans, an interferogram zero-filling factor of 64, and Blackmann-Harris three-term apodization were used. 2 ) >2 730 and 720 cm corresponding to the structural units -1 CH 2 The total area of ​​the antisymmetric in-plane deflection (rolling) (A Q ) (integration method G, limits 762 and 694 cm -1 Quantitative analysis was performed using the CH structural unit (integration method G, limits 4650, 4007 cm). -1 ) corresponds to 4323cm -1 The area of ​​the CH band (A R The ethylene content in weight percent was then normalized to the normalized absorbance (A) using a quadratic calibration curve. Q / A R ) The calibration curve was previously constructed by ordinary least squares (OLS) regression of the normalized absorbance and primary comonomer content measured on the calibration set.

[0087] Poly(propylene-co-ethylene) - Ethylene content - 13 C NMR spectroscopy quantitative 13 C{ 1 The H}NMR spectrum 1 H and 13All spectra were recorded in solution using a Bruker Avance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz for C, respectively. 13 All air pressures were recorded using nitrogen gas using a 10 mm extended temperature probe head optimized for 300 C. Approximately 200 mg of material was diluted with chromium(III) acetylacetonate (Cr(acac)) to give a 65 mM solution of the relaxation agent in the solvent. 3 ) with 3 ml of 1,2-tetrachloroethane-d 2 (TCE-d 2 ) (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, after the initial sample preparation in a heat block, the NMR tube was further heated in a rotating oven for at least 1 h. After insertion into the magnet, the tube was spun at 10 Hz. This setting was chosen mainly due to the high resolution and quantitation required for accurate ethylene content quantification. Standard single pulse excitation without NOE was employed, using an optimized tip angle, a recycle delay of 1 s, and a bilevel WALTZ16 decoupling scheme (Zhou, Z. et al., J. Mag. Reson. 187 (2007) 225 and Busico, V. et al., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were acquired per spectrum. Quantitative 13 C{ 1H} NMR spectra were processed, integrated, and relevant quantitative properties were determined from the integrals. All chemical shifts were indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This approach allowed for comparable referencing in the absence of this structural unit. Characteristic signals corresponding to ethylene incorporation were observed (Cheng, HN, Macromolecules 17 (1984), 1950), and the comonomer fraction was calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer: fE=(E / (P+E). The comonomer fraction is given by 13 C{ 1 The ethylene content was quantified using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) by integration of multiple signals over the entire spectral range of the {H} spectrum. This method was chosen for its robustness and ability to take into account the presence of positional defects when necessary. The integration region was slightly adjusted to increase applicability over the full range of comonomer contents encountered. For systems with very low ethylene content, where only isolated ethylene in the PPEPP sequence is observed, the method of Wang et al. was modified to reduce the impact of integration of sites that are no longer present. This approach reduces the overestimation of ethylene content for such systems, which was accomplished by reducing the number of sites used to determine the absolute ethylene content to E = 0.5 (Sββ + Sβγ + Sβδ + 0.5 (Sαβ + Sαγ)). With this set of sites, the corresponding integral equation can be written as E = 0.5(I H +I G +0.5(I C +I D)). The equation used for absolute propylene content was not modified. Comonomer incorporation in mole percent was calculated from the mole fraction: E[mol%]=100×fE. Comonomer incorporation in weight percent was calculated from the mole fraction: E[wt%]=100×(fE×28.06) / ((fE×28.06)+((1−fE)×42.08)).

[0088] i) Comonomer Content The content was determined by the film thickness method using the intensity I(q) of the quantitative band and the thickness T of the pressed film according to the following relationship: [I(q) / T]m+c=C, where m and c are 13 The coefficients were determined from a calibration curve constructed using the comonomer contents obtained from C-NMR spectroscopy. The comonomer content is 13 The spectra were measured in a known manner based on Fourier transform infrared spectroscopy (FTIR) using a Nicolet Magna 550 IR spectrometer with Nicolet Omnic FTIR software, calibrated with C-NMR. Films with a thickness of about 250 μm were compression molded from the samples. Similar films were made from calibration samples with known comonomer contents. The comonomer contents were measured using a 1430-1100 cm -1 The absorbance was determined from the spectrum in the wavenumber range of 1410 to 1320 cm. The absorbance was measured as the height of the peak by choosing a so-called short baseline or a long baseline or both. The short baseline was measured from about 1410 to 1320 cm through the lowest point. -1 The long baseline is about 1410~1220cm -1 An individual calibration had to be performed for each baseline type, and the comonomer content of the unknown samples was within the range of the comonomer content of the calibration samples.

[0089] j) MFR The melt flow rate (MFR) was measured at 230°C (polypropylene-based material) or 190°C (polyethylene-based material) under a load of 2.16 kg. 2Melt flow rate is the amount of polymer in grams that an ISO 1133 standardized test apparatus will extrude in 10 minutes at a temperature of 230°C (or 190°C) under a load of 2.16 kg.

[0090] k)density Density was measured according to ISO 1183-187. Sample preparation was performed by compression molding according to ISO 1872-2:2007.

[0091] l) Heat deflection temperature (HDT) HDT was prepared according to ISO 1873-2 and stored at +23°C for at least 96 hours before measurement. 3 The strength was determined on injection moulded specimens of 0.45 MPa. Tests were performed on flat supported specimens according to ISO 75, condition B, with a nominal surface stress of 0.45 MPa.

[0092] m) Coefficient of linear thermal expansion (CLTE) The coefficient of linear thermal expansion (CLTE) was determined according to ISO 11359-2:1999 on twenty 10 mm long pieces cut from the same injection-molded specimens used for the determination of the tensile modulus. Measurements were performed in the longitudinal (machine) direction in the temperature range -30 to +80 °C at a heating rate of 1 °C / min and in the temperature range 23 to +80 °C at a heating rate of 1 °C / min, respectively.

[0093] n) Paint adhesion Adhesion is characterized as the resistance of a decorative coating, such as paint, when subjected to high pressure cleaner washing according to specific conditions described below. Injection-molded sample plates (150 mm x 80 mm x 3 mm) were prepared at a melt temperature of 240 °C and a mold temperature of 50 °C. The flow front velocity was 100 mm / s. Before coating, the plaques were cleaned with Zeller Gmelin Divinol® mm / s for 5 min. The surface was then activated by flaming, where a mixture of propane (9 liters / min) and air (180 liters / min) in a ratio of 1:20 was spread over the polymer substrate with a burner at a speed of 670 mm / s. The polymer substrate was then coated with three layers: primer, base coat (black) and clear coat. The flaming process was performed twice. The decorative coating was cut into the substrate with a total depth of about 500 μm (including coating and substrate) using a cutting tool that produced a cross (intersection) with a branch of 100 mm length. Three lines with corresponding crosses were cut on each coated substrate. The cut areas were further exposed to steam of hot water having temperature T directed at an angle α from a distance d to the surface of the test panel for a time t. The pressure of the water jet results from the water flow rate and is determined by the type of nozzle installed at the end of the water pipe. The following parameters were used:

[0094] T(water) = 68°C; t = 30 sec; d = 100 mm, α = 90°, water pressure 65 bar, nozzle type = Walter 13 / 32.

[0095] Adhesion is measured as the area of ​​defective (false, rejected) or peeled coating per test line in mm 2 The peeling area was evaluated by quantifying the area by the number of test points. For each example, five panels (150 mm x 80 mm x 3 mm) were tested. For this purpose, images of the test lines were taken before and after the steam jet exposure. The peeling area was then calculated using image processing software. The average failure area for three test lines on five specimens (i.e., the average of 15 test points overall) was reported as the average failure area. SD is the standard deviation determined according to the following formula:

number

number

[0096] experiment Catalyst system: For the polymerization process of HECO1, a Ziegler-Natta type catalyst was used as described and used in the examples of WO 2016 / 066446 A1, prepolymerized with vinylcyclohexane to nucleate poly(vinylcyclohexane). Nucleation by prepolymerization with vinylcyclohexane is described in detail in EP 2960256 B1 and EP 2960279 B1, which are incorporated by reference.

[0097] For the polymerization process of HECO2 and HECO3, a high-yield MgCl transesterification with diethyl phthalate as the internal donor was used. 2 A supported Ziegler-Natta polypropylene catalyst component was used. The catalyst component and its preparation concept are generally described, for example, in patent publications EP 491566, EP 591224 and EP 586390. Therefore, the catalyst components were prepared as follows: 0.1 mole of MgCl 2 3×EtOH was suspended in 250 ml of decane in a reactor at atmospheric pressure under inert conditions. The solution was cooled to −15° C. and 300 ml of cold TiCl was added while maintaining the temperature at said temperature. 4 The temperature of the slurry was then slowly increased to 20°C. At this temperature, 0.02 moles of dioctyl phthalate (DOP) was added to the slurry. After the addition of the phthalate, the temperature was increased to 135°C over 90 minutes and the slurry was allowed to settle for 60 minutes. An additional 300 ml of TiCl 4was added and the temperature was maintained at 135° C. for 120 minutes. After this, the catalyst was filtered from the liquid and washed six times with 300 ml of heptane at 80° C. The solid catalyst component was then filtered and dried.

[0098] HECO1, HECO2 and HECO3 were produced in a prepolymerization / loop reactor / gas phase reactor 1 / gas phase reactor 2 / gas phase reactor 3 configuration followed by a pelletization step. The catalyst system defined above was used in combination with triethylaluminum (TEAL) as cocatalyst and dicyclopentadienyl-dimethoxysilane (donor D) as external donor.

[0099] [Table 1(1)] [Table 1(2)]

[0100] The heterophasic copolymers HECO1, HECO2 and HECO3 were compounded at 220° C. in a co-rotating twin screw extruder Coperion ZSK 47 with 0.15 wt. % of an antioxidant (Irganox B215FF from BASF AG, Germany, which is a 1:2 mixture of pentaerythrityl-tetrakis(3-(3′,5′-di-tert-butyl-4-hydroxyphenyl)-propionate, CAS number 6683-19-8 and tris(2,4-di-t-butylphenyl)phosphite, CAS number 31570-04-4), 0.05 wt. % of Ca stearate (CAS number 1592-23-0, commercially available from Faci, Italy). CRYSTEX QC analysis of these three copolymers gave the results listed in Table 2.

[0101] [Table 2]

[0102] Table 3 shows the properties of the polypropylene / polyethylene blends (A) used in the evaluation. The properties are shown as ranges since these compositions originate from a mechanical recycling process.

[0103] [Table 3]

[0104] Plastomer 1 is commercially available from DOW, Inc., USA, and has a viscosity of 860 kg / m 3 Density, MFR <0.5g / 10min 2 The polymer was Engage HM7487, an ethylene-1-butene plastomer having a melting point of 1.25 mm (2.16 kg, 190° C., ISO 1133).

[0105] Plastomer 2 is commercially available from DOW, Inc., USA, 857 kg / m 3 Density and MFR of 1.0g / 10min 2 (2.16 kg, 190° C., ISO 1133).

[0106] Talc 1 is commercially available from IMERYS, France, and has a diameter of 1.2 μm. 50 and d of 3.3 μm 95 The chromatogram was obtained using a Jetfine 3CA with Sedigraph measurement.

[0107] Talc 2 is commercially available from IMERYS, 2.0 μm d 50 and d of 10.0 μm 95 The fluororesin was Luzenac HAR T84 with Sedigraph measurement.

[0108] PP-homo has an MFR of 1200g / 10min. 2 The polymer was a commercially available propylene homopolymer HL712FB having a viscosity of 1.2 kg, 230° C., ISO 1133 and a Tm of 158° C. (DSC, ISO 11357-3).

[0109] The final compositions were compounded using the above polymers and talc along with antioxidants, UV stabilizers, slip agents, nucleating agents, carbon black masterbatch, calcium stearate, antifog agents in a Coperin ZSK40 twin screw extruder at 220° C. The compositions of the examples performed are shown in Table 4.

[0110] [Table 4]

[0111] Table 5 shows the characteristics of the examples carried out.

[0112] [Table 5] nm = not measured.

[0113] Example IE2 shows that by using HECO1 instead of HECO2 in CE2, better mechanical properties and better thermal stability can be obtained at comparable impact properties, flow and good paint adhesion. Example IE1 shows that by omitting HECO3, flow can be further improved without sacrificing other properties. The addition of PP-Homo in examples IE3 and IE4 shows an increase in flowability, which allows for exceptional mechanical behavior and thermal stability when using a lower amount of plastomer in IE4. However, the addition of PP-Homo comes at the expense of impaired paintability.

Claims

1. A composition suitable for automotive applications obtained by blending at least components (A), (B), (C) and (D), (A) 15% to 50% by weight of a mixed plastic polypropylene blend; (B) 20% to 50% by weight of a heterophasic propylene copolymer; (C) 5% to 25% by weight of an ethylene-based plastomer, and (D) 5% by weight to 25% by weight of an inorganic filler; All percentages are given relative to the total composition. The mixed plastic polypropylene blend (A) is Originating from post-consumer and / or industrial waste and containing polypropylene and polyethylene; A crystalline fraction (CF) content determined according to CRYSTEX analysis obtained by temperature cycling of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from 85.0 to 96.0% by weight; and Soluble fraction (SF) content determined according to CRYSTEX analysis obtained by temperature cycle of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from 4.0 to 15.0% by weight. having The crystalline fraction (CF) is in the range of 1.0 to 10.0% by weight. 13 having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; The soluble fraction (SF) has an intrinsic viscosity (iV(SF)) measured in decalin according to DIN ISO 1628 / 1 at 135° C. in the range of 0.9 to 2.1 dl / g, The heterophasic propylene copolymer (B) comprises a matrix phase and an elastomeric phase dispersed therein, detectable by high resolution microscopy; Melt flow rate (MFR) of 85 to 250 g / 10 min 2 (230℃, 2.16kg, ISO1133), a soluble fraction (SF) content determined according to CRYSTEX analysis obtained by temperature cycling of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from greater than 20.0% by weight to 30.0% by weight; and the intrinsic viscosity iV(SF) of the soluble portion, measured in decalin according to DIN ISO 1628 / 1 at 135° C., of 2.0 dl / g to 4.5 dl / g having The ethylene-based plastomer (C), which is a copolymer of ethylene and a comonomer unit selected from an α-olefin having 3 to 12 carbon atoms, is Melt flow rate (MFR) of 0.2 to 2.5 g / 10 min 2 (190°C, 2.16 kg, ISO1133), and 850-870kg / m 3 Density of having The composition comprises: Melt flow rate (MFR) of 8 to 50 g / 10 min 2 (230℃, 2.16kg, ISO1133) A composition comprising:

2. It is obtained by blending components (A), (B), (C), (D) and one or more of the following components: (E) 0-20 wt. % of a second heterophasic propylene copolymer, and (F) 0 to 10% by weight of a propylene homopolymer; All percentages are given relative to the total composition. said second heterophasic propylene copolymer (E) comprises a matrix phase and an elastomeric phase dispersed therein, detectable by high resolution microscopy; Melt flow rate (MFR) of 2 to 10 g / 10 min 2 (230℃, 2.16kg, ISO1133), a soluble fraction (SF) content determined according to CRYSTEX analysis obtained by temperature cycling of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. of greater than 20.0 to 50.0% by weight; and The intrinsic viscosity iV(SF) of the cold xylene solubles (XCS) content between 4.0 dl / g and 10.0 dl / g of said solubles, measured in decalin according to DIN ISO 1628 / 1 at 135°C having The propylene homopolymer (F) is Melt flow rate (MFR) of 800 to 2000 g / 10 min 2 (230℃, 2.16kg, ISO1133) 2. The composition of claim 1 having the formula:

3. obtained by blending components (A), (B), (C) and (D), in the absence of (E) a second heterophasic propylene copolymer, and (F) a propylene homopolymer; (A) 15% to 50% by weight of a mixed plastic polypropylene blend; (B) 30% to 50% by weight of a heterophasic propylene copolymer; (C) 5% to 25% by weight of an ethylene-based plastomer, and (D) 5% by weight to 25% by weight of an inorganic filler; The composition of claim 1.

4. obtained by blending components (A), (B), (C), (D) and (E), in which (F) propylene homopolymer is not present; (A) 15% to 40% by weight of a mixed plastic polypropylene blend; (B) 20% to 50% by weight of a heterophasic propylene copolymer; (C) 5% to 25% by weight of an ethylene-based plastomer; (D) 5% to 25% by weight of an inorganic filler, and (E) 5% to 20% by weight of a second heterophasic propylene copolymer; The composition of claim 1.

5. obtained by blending components (A), (B), (C), (D) and (F), in the absence of (E) a second heterophasic propylene copolymer; (A) 15% to 40% by weight of a mixed plastic polypropylene blend; (B) 20% to 50% by weight of a heterophasic propylene copolymer; (C) 5% to 25% by weight of an ethylene-based plastomer; (D) 5% to 25% by weight of an inorganic filler, and (F) 2% to 10% by weight of a propylene homopolymer The composition of claim 1.

6. The inorganic filler (D) is Median particle size before compounding d from 0.3 to 30.0 micrometers 50 and / or Top cut particle size before compounding d from 1.0 to 50.0 micrometers 95 The composition of claim 1 which is a talc having the formula:

7. A crystalline fraction (CF) content determined according to CRYSTEX analysis obtained by temperature cycling of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from 55.0 to 75.0% by weight; and Soluble fraction (SF) content determined according to CRYSTEX analysis obtained by temperature cycle of dissolution at 160° C., crystallization at 40° C. and redissolution in 1,2,4-trichlorobenzene at 160° C. ranging from 25.0 to 45.0% by weight. having The crystalline fraction (CF) is quantitatively less than 10.0% by weight. 13 having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; The crystalline fraction (CF) has an intrinsic viscosity (iV(CF)), measured in decalin according to DIN ISO 1628 / 1 at 135° C., of less than 1.8 dl / g; The soluble portion (SF) is in the range of 45.0 to 65.0% by weight. 13 having an ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy; The soluble fraction (SF) has an intrinsic viscosity (iV(SF)) measured in decalin according to DIN ISO 1628 / 1 at 135° C. of more than 1.6 dl / g. The composition of claim 1.

8. 2. The composition of claim 1 having a flexural modulus of 1400 MPa to 2000 MPa.

9. 20.0 kJ / m 2 ~65.0 kJ / m 2 and / or a Charpy notched impact strength at 23°C of 4.0 kJ / m 2 ~10.0 kJ / m 2 2. The composition of claim 1, having a Charpy notched impact strength at -20°C of

10. 2. The composition of claim 1 having a deflection temperature under load (ISO 75B) of greater than 90° C. and / or a coefficient of linear thermal expansion (CLTE) of 60 to 100 μm / mK.

11. 2. The composition of claim 1 having a puncture energy of 25 to 55 J when determined in an instrumented drop weight test according to ISO 6603-2 at 23°C, and / or a puncture energy of 12 to 40 J when determined in an instrumented drop weight test according to ISO 6603-2 at -30°C.

12. An article comprising the composition of any one of claims 1 to 11.

13. 50mm 2 Less than, mm 2 having paint adhesion rated as a unit of failed or delaminated coating area; 13. The article of claim 12, wherein the coating area is determined by coating a primer layer, a base coat (black) layer, and a clear coat layer on an injection molded sample plate of 150 mm x 80 mm x 3 mm, cutting the coating with a cutting tool that creates a cross with 100 mm long branches, exposing the cut area to water at 68°C, and calculating the peel area using image processing software.

14. 12. Use of a composition according to any one of claims 1 to 11 for injection moulding of an article.

Citation Information

Patent Citations

  • Polypropylene composition

    JP1983168649A

  • Multilayer plastic vessel

    JP1994320689A

  • Polypropylene composition

    JP1997208797A

  • Ultra-high molecular weight polyethylene-made porous sintered body

    JP2016176061A

  • Polypropylene-polyethylene composition with improved flowability

    JP2018532859A